2018
DOI: 10.33750/ijhi.v1i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the motivation, participation, and achievement of students

Abstract: This research focused on students’ motivation, class participation and achievement in male and female class as well as mixed class. The research used the quantitative method to investigate the students’ motivation, participation, and achievement in different classroom composition. The findings of this research indicated that there is no difference in students’ motivation in gender-based EFL classroom. Male class gained the highest scores in performance goal and achievement goal in factors of motivation. Meanwh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…In terms of gender, boys seem to be more motivated than girls. Our findings are supported by the results obtained in other studies (see, e.g., Akib et al, 2018;Dilshad et al, 2019). Furthermore, using Internet outside school during longer periods is associated with lower levels of motivation to study.…”
Section: Econometric Estimatessupporting
confidence: 94%
“…In terms of gender, boys seem to be more motivated than girls. Our findings are supported by the results obtained in other studies (see, e.g., Akib et al, 2018;Dilshad et al, 2019). Furthermore, using Internet outside school during longer periods is associated with lower levels of motivation to study.…”
Section: Econometric Estimatessupporting
confidence: 94%
“…Furthermore, it was found that the collaborative communication activities preferred by the students can be done during learning interaction and outside of the class to make them more collaborative one another to minimize the gap among them. Communicative activities cover various activities that encourage and engage learners in communicating and sharing with other students (Akib, Haryanto, Iskandar, & Patak, 2018;Nunan, 1989), and with community or people they meet in their daily life. It also has real aims in sharing information, breaking down barriers among them, and discussing themselves and any issues around them.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, project-based learning provides opportunities for "the natural integration of language skills" (Stoller, 2006). A further benefit is that because project work progresses according to the specific context and students' interests (Blumenfeld et al, 1991), students have enhanced motivation, engagement, and enjoyment (Akib, Haryanto, Iskandar, & Patak, 2018;Lee, 2002). From a motivational perspective, projects being authentic tasks, are more meaningful to students, increase interest, motivation to participate, and can promote learning (Brophy, 2013).…”
Section: Resultsmentioning
confidence: 99%